Penggunaan Serat Eceng Gondok Dalam Campuran Laston Tipe V SNI 03-1737-1989 Terhadap Indeks Marshall Properties - Agus Tonny Arifianto; Zulkifli Lubis (Litbang Pemas - Universitas Islam Lamongan, 2019)
Road is one of the most important transportation infrastructures in the development progress of society's live. Pavement structure has an important role in providing optimal service. Traffic loads that exceed the limit conditions often occur,for there is a certain consideration in planning the asphalt mixture, including improving the asphalt quality. The idea to modify asphalt materials with admixture materials is expected to enlarge the asphalt attachment energy to the stone. One of them is using water hyacinth fiber. This study aims to find out the effect of water hyacinth fiber addition to the characteristics of Type V SNI 03-1737-1989 asphalt concrete mixture on the Marshall test index. The method used is experimental method. Laboratory testing is conducted using water hyacinth fiber to the mixture of Type VSNI 03-1737-1989 asphalt concrete as the aditional material with variations of 1%, 1.5%, 2%, 2.5% and 3% of total asphalt weight in the mixture on asphalt condition optimum 5.72%. The results of Marshall Stability increases by 5.88%, plastic melting (flow) increases by 9%,void in the mix increases by 38.59%, void filled with asphalt decreases by6.54%, void in mineral aggregate increases by 5.60%, the density of the mixture increases by 2.59% and Marshall Quotient decreases by 3.38%.